O.N.T. Magazine, September 1938 (Confluenţe Bibliologice, 2021)
This article provides information about other articles from O.N.T. magazine, September 1938, such as: The tourist landscape in Romania, The most beautiful roads in the country, On the Hell’s Valley. From these materials, it points some passages related to the rhythm in which the values of national patrimony are discovered. This magazine from September 1938, presents an interesting autumn itinerary dedicated to the Danube Delta. At the end, the markings with the red triangle, the blue horizontal line and the blue vertical line on the range of the Ezer-Papusa Muscel Mountains are mentioned. The mountain and sea Guard Camps are not omitted.
Keywords: National Tourism Office Magazine